The Influence of Infrastructure and Work Environment on Teacher Performance in State Junior High Schools in Mesuji Raya District - Puput Nirwana; Tri Widayatsih; Nila Kesumawati (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2025)
The purpose of this study is to describe and analyze 1). To describe and analyze the influence of infrastructure on teacher performance in Junior High Schools in Mesuji Raya District 2). To describe and analyze the influence of the work environment on teacher performance in Junior High Schools in Mesuji Raya District 3). To describe and analyze the influence of infrastructure and work environment on teacher performance in Junior High Schools in Mesuji Raya District. This study uses a quantitative method with a correlational research type. The sample of this study was conducted at 5 Junior High Schools in Mesuji Raya District with a total of 53 teachers. Data collection techniques used questionnaires and documentation. Data analysis techniques used correlation and multiple regression analysis techniques using the SPSS version 26 application. The results of this study indicate that there is an influence of infrastructure and work environment variables together on the performance of Junior High School teachers in Mesuji Raya District by 72.8% and the remaining 27.2%. influenced by other factors not mentioned in this study.